Uji Anti Hiperglikemik Ekstrak Etanol Daun Salam (Syzygium Polyanthum (Wight.) Walp) Dan Daun Cepcepan (Castanopsis Costata (Blume) A. Dc.) Terhadap Tikus Putih - Devortivo Hartono Putra; Erida Novriani; Razoki (CV. ITTC INDONESIA, 2025)
Hyperglycemia, characterized by elevated blood glucose levels, is a key clinical feature of diabetes mellitus. In recent years, medicinal plants have gained attention as alternative therapies due to their relatively minimal side effects. This study aimed to explore the potential of acombined ethanol extract of bay leaf (Syzgium polyanthum) and cepcepan leaf (castanopsis costata) in lowering blood flucose leveles in white rats (Rattus norvegicus) induced with alloxan. The extraction process was carried out using the maceration methos with 96% ethanol. Phytochemical screening revealed the presence of active compounds such as flavonoids, alkoloids, tannins, saponins, and steroid. The rats were divided into six groups: a normal group. A negative control group (alloxan only), a positive control group (glibenclamide 0.45 mg/kgBB), and three treatment groups receiving the combined extract at doses of 120 mg/kgBW, 250mg/kgBW, and 500mg/kgBW. Blood glucose levels were monitored from day 0 to day 15. ANOVA analysis showed a reduction in glucose levels among the treatment groups, althought the results were not statistically significant (p > 0.05). nevertheless, a consistent downward trend was observed, particularyl in the group receiving 250mg/kgBW. These findings suggest that the ethanol extract combination of bay and cepcepan leaves holds promise as an antihyperlycemic agent. However, frurther research is necessary to confirm its efficacy and fully understand its mechanism of action.